2018
DOI: 10.1039/c7ra13028g
|View full text |Cite
|
Sign up to set email alerts
|

The impact of microRNA-122 and its target gene Sestrin-2 on the protective effect of ghrelin in angiotensin II-induced cardiomyocyte apoptosis

Abstract: Ghrelin with n-octanoylated serine 3 residue is a peptide hormone with well-known cardioprotective properties.MicroRNA-122 is associated with the pathogenesis of many cardiovascular diseases, including apoptosis and was found highly increased in our previous rat model of post-myocardial infarction heart failure. In this study, we aimed to identify the target gene of microRNA-122 and to evaluate their impacts on the protective effect of acylated ghrelin in angiotensin II-induced apoptosis. The results showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Noncoding RNAs exert transcriptional and translational modifications and modulate signaling pathways in diabetic nephropathy [153]. It has been observed that several noncoding RNAs regulate Sestrin2 expression [154,155]. For instance, microRNA-122 delivery or inhibition of miR-148b-3p and miR-199a-5p increased Sestrin2 expression in animal studies and cell culture in previous studies [154,155].…”
Section: The Potential Of Noncoding Rnas In Regulating Sestrin2 Signa...mentioning
confidence: 99%
“…Noncoding RNAs exert transcriptional and translational modifications and modulate signaling pathways in diabetic nephropathy [153]. It has been observed that several noncoding RNAs regulate Sestrin2 expression [154,155]. For instance, microRNA-122 delivery or inhibition of miR-148b-3p and miR-199a-5p increased Sestrin2 expression in animal studies and cell culture in previous studies [154,155].…”
Section: The Potential Of Noncoding Rnas In Regulating Sestrin2 Signa...mentioning
confidence: 99%
“…Recently, it was shown that non-coding RNAs are heavily involved in different stages of gene expression in cancer cells and interact with oncogenes, tumor-suppressor genes, and oncogenic signaling pathways [ 56 , 142 ]. New techniques such as non-coding RNAs delivery and vector systems can contribute to regulating the gene expression of Sestrin2 in cancer [ 118 , 143 ]. These methods of treatment as well as direct targeting of Sestrin2 can be used in future clinical trials.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%
“…Table 1 indicates the single-stranded primers used for the synthesis of the cDNAs corresponding to the particular miRNA, namely miRNA-21, miRNA-122, miRNA-221, and U6 which was used as a housekeeping gene. (13) miR-122 GTCGTATCCAGTGCAGGGTCCGAGGTGCACTGGATACG ACCAAACAC RT (Wang et al, 2018) (14) miR-221 GTCGTATCCAGTGCGTGTCGTGGAGTCGGCAATTGCAC TGGATACGACGAAACCC RT (Gong and Gong, 2018) (15) U6 CGCTTCACGAATTTGCGTGTCAT RT (Wang et al, 2018) (14) Complementary DNA was synthesized by utilizing total RNA as a template and the use of ProtoScript® First Strand cDNA Synthesis Kit according to the instructions of the manufacturing company. The following program was applied for the generation of cDNAs (Table 2).…”
Section: Molecular Investigationmentioning
confidence: 99%
“…Four primes' sets (Forward and reverse) were used for the amplification of the cDNA of interest (Table 3). (13) miR-122 F 3´ TGCGGTTGGAGTGTGACAATGG 5´ R 3´CAGTGCAGGGTCCGAGGT 5´ (Wang et al, 2018) (14) miR-221 F 3´ GGAGCTACATTGTCTGCTGG 5´ R 3´ CAGTGCGTGTCGTGGAGT 5´ (Gong and Gong, 2018) (15) U6 F 3´ CTCGCTTCGGCAGCACA 5´ R 3´AACGCTTCACGAATTTGCGT 5´ (Wang et al, 2018) (14) The reaction components with their relevant volumes are demonstrated in Table 4. The qRT-PCR reaction conditions were programmed as shown in Table 5.…”
Section: Real Time-quantitative Pcr (Rt-qpcr)mentioning
confidence: 99%